"HIDDEN STRUGGLES: A COMPREHENSIVE SOCIAL RESEARCH STUDY ON DRUG ADDICTION IN KASHMIR": - Mohd Arif Naikoo; Arif Hussain Pandith (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Drug addiction is an escalating social issue worldwide, with profound implications for individuals and societies. Kashmir, a region already beset by political instability and conflict, faces a burgeoning drug addiction crisis. This paper delves into the causes, prevalence, and impact of drug addiction in Kashmir, examining the socio-economic and political factors that exacerbate this issue. Through a comprehensive review of existing literature, qualitative interviews, and analysis of social trends, this research aims to provide a holistic understanding of the drug addiction epidemic in Kashmir and suggest possible interventions.